ADHD, Lifestyles and Comorbidities: A Call for an Holistic Perspective – from Medical to Societal Intervening Factors - Weissenberger, Simon; Ptacek, Radek; Klicperova-Baker, Martina; Erman, Andreja; Schonova, Katerina; Raboch, Jiri; Goetz, Michal (Frontiers in Psychology, 2017)
The review examines Attention Deficit Hyperactivity Disorder (ADHD in its Child and Adult form) and its various presentations (Hyperactive Impulsive, Inattentive and Combined) with a particular focus on environmental & social factors and comorbidities. It is argued that ADHD is best understood in a holistic and interactive context and a vast empirical literature is presented to illustrate the point: Environmental factors include stress in general as well as exposure to toxins (phthalates, bisphenol A). Social factors are illustrated by effects of social deprivation, maternal lifestyle during pregnancy (particularly those which are associated with nicotine, alcohol, caffeine and drug dependencies or with exposure to seemingly benign medications like acetaminophen, which all tend to be related to ADHD; family environment is discussed with respect to predictive or protective effect of (mainly authoritative and autocratic) parenting styles. Societal factors include mainly economic and political issues: problems of income inequality and poverty (low SES is an ADHD risk factor) and a growing moral dilemma between a humanistic effort to globally spread the knowledge of ADHD, and the medicalization and commercialization the disorder. The second part of the review is devoted to ADHD related lifestyles and resulting comorbidities (e.g., food addiction and obesity, substance abuse, electronic media dependencies and conduct & personality disorders). Although ADHD is a neurodevelopmental disorder, its assessment and treatment are also linked to environmental, behavioral and social factors and their interactions described in this article.